FINANCIAL DETERMINANTS OF SMEs GROWTH IN THE TIME OF ECONOMIC - Marina Jeger; Nataša Šarlija; Ana Bilandžić (Ekonomski Vjesnik, 2016)
The importance of high-growth enterprises in national economies has been widely substantiated by economic research in recent years. There are a small number of papers that investigate determinants of growth in the time of economic downturn. This paper is focused on finding financial ratios that are determinants of growth in small and medium-sized enterprises (SMEs) which operate in downturn economies. The assumption of this study is that the time of economic downturn sets new challenges to SMEs and that fact should be reflected in their financial statements as well as in the growth prediction model. Our hypotheses have been tested on the sample of 1492 SMEs from Croatia over the period 2008-2013 in the time of economic downturn. Using logistic regression, a growth prediction model has been developed and tested. Results have shown that in the time of economic downturn, growth potential of SMEs increases with the increase of liquidity, turnover and profitability and with the decrease of leverage.